2015
DOI: 10.1007/s00384-015-2291-x
|View full text |Cite
|
Sign up to set email alerts
|

Low anterior resection combined with a covering stoma in the treatment of rectal cancer reduces the risk of permanent anastomotic failure

Abstract: Our standardized surgical regimen with a covering stoma in low anterior resection for rectal cancer resulted in a minor anastomosis failure rate and a low risk of permanent stoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
5
0
3
Order By: Relevance
“…The tailored surgery in deep infiltrated bowel endometriosis is strongly recommended by most specialists experienced in surgery conducted in endometriosis [14,15]. Some centers recommend and perform protective stoma for all low rectum resections [16,17], while others recommend them for patients who have other intraoperative risk factors for leakage [18]. In our group, protective stoma was performed only in a few very complex cases and one case of a very low resection that led to the rate of 2.9% in the entire segmental bowel resection group (138 patients).…”
Section: Discussionmentioning
confidence: 99%
“…The tailored surgery in deep infiltrated bowel endometriosis is strongly recommended by most specialists experienced in surgery conducted in endometriosis [14,15]. Some centers recommend and perform protective stoma for all low rectum resections [16,17], while others recommend them for patients who have other intraoperative risk factors for leakage [18]. In our group, protective stoma was performed only in a few very complex cases and one case of a very low resection that led to the rate of 2.9% in the entire segmental bowel resection group (138 patients).…”
Section: Discussionmentioning
confidence: 99%
“…The dramatic results and the unaffordable high rate of anastomotic leak, especially for rectal operations, have directed colorectal institutions to adopt and recommend different techniques to limit the consequences of anastomotic leak, including diverting defunctioning loop ileostomies for single low anterior resections, 29,30 trans-anal drainage tubes, trans-anal sponge and other systems of drainage. 31,32 Even if it has been recognised, the fact that the diverting stomas limit the sequels of the anastomotic leak rather its occurrence, a Swedish trial concluded to a reduction of the rate of anastomotic leakage from 28% to 10.3% in patients randomised to a stoma. 29 Recent clinical and experimental studies confirm the presence of new molecular targets and biomarkers in the field of diabetic wound healing.…”
Section: Conclusion and Implications For Future Researchmentioning
confidence: 99%
“…Consequently, the number of cases requiring diverting stoma (DS) creation has increased. A consensus was reached regarding DS construction during rectal cancer surgery to prevent severe peritonitis related to anastomotic leakage [2][3][4][5]. Anastomotic leakage significantly reduces patients' quality of life (QOL); therefore, the prevention of anastomotic leakagerelated severe peritonitis is crucial.…”
Section: Introductionmentioning
confidence: 99%